2023
DOI: 10.1111/cns.14090
|View full text |Cite
|
Sign up to set email alerts
|

The influence of NQO2 on the dysfunctional autophagy and oxidative stress induced in the hippocampus of rats and in SH‐SY5Y cells by fluoride

Abstract: Introduction For investigating the mechanism of brain injury caused by chronic fluorosis, this study was designed to determine whether NRH:quinone oxidoreductase 2 (NQO2) can influence autophagic disruption and oxidative stress induced in the central nervous system exposed to a high level of fluoride. Methods Sprague–Dawley rats drank tap water containing different concentrations of fluoride for 3 or 6 months. SH‐SY5Y cells were either transfected with NQO2 RNA interference or treated with NQO2 inhibitor or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It also was identified as one of the most prominent factors involved in neurodegeneration 50 , 51 , whereas Atf4 was reported as an unequivocally prodeath neuronal transcriptional factor, strongly implicated in Parkinson’s disease 52 , 53 , similarly to Egr1 54 , 55 . ROS-activation driven overexpression of Nqo2 has been identified in preclinical model and neuropsychiatric disorders 56 , 57 . Hdac4 was reported to play a pivotal role in the pathogenesis of ischemic stroke and post-stroke recovery by affecting neuronal death, angiogenesis, and neurogenesis 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It also was identified as one of the most prominent factors involved in neurodegeneration 50 , 51 , whereas Atf4 was reported as an unequivocally prodeath neuronal transcriptional factor, strongly implicated in Parkinson’s disease 52 , 53 , similarly to Egr1 54 , 55 . ROS-activation driven overexpression of Nqo2 has been identified in preclinical model and neuropsychiatric disorders 56 , 57 . Hdac4 was reported to play a pivotal role in the pathogenesis of ischemic stroke and post-stroke recovery by affecting neuronal death, angiogenesis, and neurogenesis 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It also was identi ed as one of the most prominent factors involved in neurodegeneration [43,44], whereas Atf4 was reported as an unequivocally prodeath neuronal transcriptional factor, strongly implicated in Parkinson's disease [45,46], similarly to Egr1 [47,48]. ROSactivation driven overexpression of Nqo2 has been identi ed in preclinical model and neuropsychiatric disorders [49,50]. Hdac4 was reported to play a pivotal role in the pathogenesis of ischemic stroke and post-stroke recovery by affecting neuronal death, angiogenesis, and neurogenesis [51].…”
Section: Discussionmentioning
confidence: 99%
“…The toxifying function of NQO2, anticipated in the introduction, was first described in the case of menadione [39], then for a series of substrates and other unrelated compounds [11,13,40,41]. For example, it was reported that NQO2 mediates the generation of ROS by acetaminophen, and thus its toxicological side-effects [42], leading to a new concept that NQO2, despite its reductase capacity, might have been under special circumstances an enzyme that indirectly leads to the enhancement of ROS production.…”
Section: The Role Of Nqo2 In Drug Metabolismmentioning
confidence: 99%